Influencia en los medios audiovisuales en el aprendizaje de los adolescentes del Colegio José María Velasco Ibarra en Buena Fe año 2021 - Mise Anchundia, Arianna Nicolle (2021)
The objective of this research is to instill information about the audiovisual media that can serve them in their day-to-day lives, now currently the students of the José María Velasco Ibarra Educational Unit use it frequently when receiving classes and uploading their homework. The audiovisual media are accessible to everyone and have a growing power of influence in the home. They allow us to gather complex techniques and elements that seek to be at the forefront in the use of the media, audiovisual media become tools of great value in both face-to-face, distance and as didactic aids in the teacher's practice.